2021
DOI: 10.1017/s1368980021000951
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ knowledge, attitudes and practices regarding probiotic use during pregnancy and for their infants in Turkey

Abstract: Objective: This study was conducted to determine mothers’ knowledge, attitudes, and practices regarding probiotic use during pregnancy and for infants between six months and two years old. Design: The study had a cross-sectional design, and the data were collected using a Sociodemographic Information Form and a Probiotic Information and Attitude Form. The data were evaluated using frequency, percentage and chi-square tests. Setting: Two hospitals of one province in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…In another study in 2012, Cevik Guner et al [31] found that the level of education and type of occupation of mothers in Turkey were associated with the level of probiotic knowledge. Similarly, in another study conducted by Aslan et al in 2019 [37] the level of probiotic knowledge increased as the level of education increased in adults.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In another study in 2012, Cevik Guner et al [31] found that the level of education and type of occupation of mothers in Turkey were associated with the level of probiotic knowledge. Similarly, in another study conducted by Aslan et al in 2019 [37] the level of probiotic knowledge increased as the level of education increased in adults.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we aimed to evaluate the relationship between microbiota awareness in the first trimester and the diagnosis of a high-risk pregnancy. Upon reviewing the literature, it was determined that studies evaluating microbiota/probiotic knowledge in health professionals, university students and mothers [29][30][31][32] exist, but there are no studies evaluating this knowledge in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the study concluded that the participants had a confusion regarding general information, product information, chronic disease, and probiotic and prebiotic subdimensions, and that they could not establish the relationship between microbiota and diseases such as Alzheimer's disease, celiac disease, obesity, diabetes, and bowel cancer. Similarly, several studies have highlighted that people lack understanding about the relationship between microbiome and diseases 8 , 11 , 13 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic knowledge levels are generally low in our country. In another study conducted on mothers in Turkey, it was found that the level of education and occupation of the mother were associated with the level of probiotic knowledge [40]. Similarly, in another study evaluating adult individuals, it was shown that the level of probiotic knowledge increased as the level of education increased [41].…”
Section: Discussionmentioning
confidence: 99%